Does engagement in HIV care affect screening diagnosis and control of noncommunicable diseases in sub-Saharan Africa: a systematic review and meta analysis - Kileel, E.; Zheng, Amy; Bor, Jacob; Fox, Matthew; Crowther, Nigel; George, Jaya; Khoza, Siyabonga; Rosen, Sydney; Venter, Willem; Raal, Frederick; Hibberd, Patricia; Brennan, Alana (Springer, 2024)
Low- and middle-income countries are facing a growing burden of noncommunicable diseases (NCDs). Providing HIV treatment may provide opportunities to increase access to NCD services in under-resourced environments. We conducted a systematic review and meta-analysis to evaluate whether use of antiretroviral therapy (ART) was associated with increased screening, diagnosis, treatment, and control of diabetes, hypertension, chronic kidney disease, or cardiovascular disease among people living with HIV in sub-Saharan Africa (SSA). A comprehensive search of electronic literature databases for studies published between 01 January 2011 and 31 December 2022 yielded 26 studies, describing 13,570 PLWH in SSA, 61% of whom were receiving ART. Random effects models were used to calculate summary odds ratios (ORs) of the risk of diagnosis by ART status and corresponding 95% confidence intervals (95% CIs), where appropriate. ART use was associated with a small but imprecise increase in the odds of diabetes diagnosis (OR 1.07; 95% CI 0.71, 1.60) and an increase in the odds of hypertension diagnosis (OR 2.10, 95% CI 1.42, 3.09). We found minimal data on the association between ART use and screening, treatment, or control of NCDs. Despite a potentially higher NCD risk among PLWH and regional efforts to integrate NCD and HIV care, evidence to support effective care integration models is lacking.
Keywords: Type 2 diabetes mellitus; Hypertension; Chronic kidney disease; Cardiovascular disease; HIV/AIDS; sub-Saharan Africa; Antiretroviral therapy; SDG-3: Good health and well-being